Is this correct: Problem #13 Solve: 9x^2 = 14 I did the following i divided 9 by both sides then i get this: x^2 = 1.5555555 then i squared both sides and i got the following answer: x = 1.24 I would not have used decimals x^2 = 14/9 x= +/- (√14)/3 Yes, except you actual...
how do i find the following: is there a formula for this? Problem #15 Find the constant term that should be added to make the following expression a perfect square trinomial. x^2+7x square a few binomials and see if you can see a pattern e.g. (x+3)^2 = x^2 + 6x + 9 (x-7)^2 = x...
how can i simplify this more its for the following problem: Problem #22 solve by using the quadratic formual. 5x^2-4x+1=0 this is where i am but i do not know how to go further. x = (4 (+/-) sqrt (-4))/(10) Problem #23 Solve by completing the square. 4x^2+2x-3=0 i started usin...
okay i am getting confuse with the decimals and fractions in order to make a table for the following problem.can someone help me make the tables the problem reads as follows. solve the system. 5x-3y=13 4x-3y=11 Now, i know i have to break them to the form of y=mx+b inorder to ...
so then for -4.33333 would be in a fraction -13/3 IF the 333's are repeating. Yes.
how do you change the following decimal into a fraction. -3.6666666 3 2/3 or 11/3 Memorize .666666 repeating as 2/3 Now if the sixes do not repeat forever, the fraction can be found as 36666666/1000000 which probably can be reduced some... thats right thank you test.
Is this correct: Solve: (x+5)^2 = 3 I get: x = -5 (+/-) sqrt (3) Problem #2 Solve: 5(x-2)^2 = 3 I get: x = 3 (+/-) ((sqrt(3))/(5) No on the second. YOu have take the sqrt5 slso, so x= 2+- sqrt(3/5) correct on the first.
i am lost with this one. Solve the system by graphing. what is the soltion. 2x-2y=10 x+y=3 x=4 This is how the problem is with all thre equations. Help me please..... put it in slope intercept form. put both lines in slope intercept form. 2x-2y=10 x+y=3 y= x-5 y= -x + 3 now, p...
is this correct: rewrite the equation 4x-10y = 11 as a function of x. My answer: f(x) = 0.4x-1.1 ok
how can i rewrite the following inequality in the form y = mx + b f(x) > x you can't change an inequality into an equality. were you thinking something like f(x) > 1x + 0 ?? no this is how its written in my homework thats why i am confused .